Conference – 1992 Equation (1)

Δ p t = α 0 + i = 1 n β i Δ p t i + ε t MathType@MTEF@5@5@+= feaagKart1ev2aaatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbuLwBLn hiov2DGi1BTfMBaeXatLxBI9gBaerbd9wDYLwzYbItLDharqqtubsr 4rNCHbGeaGqiVu0Je9sqqrpepC0xbbL8F4rqqrFfpeea0xe9Lq=Jc9 vqaqpepm0xbba9pwe9Q8fs0=yqaqpepae9pg0FirpepeKkFr0xfr=x fr=xb9adbaqaaeGaciGaaiaabeqaamaabaabaaGcbaGaeuiLdqKaae iCamaaBaaaleaacaqG0baabeaakiabg2da9iabeg7aHnaaBaaaleaa caaIWaaabeaakiabgUcaRmaaqahabaGaeqOSdi2aaSbaaSqaaiaadM gaaeqaaOGaeuiLdqKaaeiCamaaBaaaleaacaqG0bGaeyOeI0IaaeyA aaqabaGccqGHRaWkcqaH1oqzdaWgaaWcbaGaaeiDaaqabaaabaGaae yAaiabg2da9iaaigdaaeaacaqGUbaaniabggHiLdaaaa@4F98@